COLOUR PSYCHOLOGY POTENTIAL IN LITHUANIAN ADVERTISING - Justinas Kisieliauskas; Evelina Sinevičiūtė (Baltic Journal of Economic Studies, 2023)
The study examines the potential of colour psychology in Lithuanian advertising, acknowledging that the application of colour psychology may vary among countries. The theoretical overview outlines the concept of colour psychology and evaluates its use in advertising. The research objective is to assess how colour psychology can be effectively implemented in Lithuanian advertising campaigns. The study aims to explore the potential of colour psychology in Lithuanian advertising. The analysis will investigate the use of colour psychology in Lithuanian advertising. Methodology of the study included a review of the scientific literature and two structured questionnaire surveys of both consumers and industry experts. The study showed that when comparing user and expert surveys, both groups agreed that properly selected colours that evoke positive emotions have a strong influence on consumer emotions and even actions. However, when comparing the theory with the results obtained in the user questionnaire, it appears that Lithuanians assign slightly different associations to corresponding colours than foreign authors. Carefully selected colours that evoke positive emotions in advertisements can attract consumers' attention and potentially encourage purchases of the depicted brand. In order to choose the right colours to communicate in advertisements, it is important to analyse the audience to which the advertisement will be presented and to clarify the values that the brand cherishes and what the specific colour used in the advertisement is intended to tell consumers about the product or service.